Public Assistance Orthodontic Treatment Needs: A Report from the State of Indiana - Jeffrey A. Dean, DDS, MSD; Shelley M. McDonald, BA; Paul 0. Walker, DDS, MSD (Blackwell Synergy, 2005)
To determine how many of the orthodontic cases covered by Indiana Medicaid between 1999-2001 would be classified pretreatment as having a malocclusion severe enough to warrant treatment.